PROGNOSIS OF PATIENTS WITH BREAST CANCER RELATED TO THE TIMING OF OPERATION DURING MENSTRUAL CYCLE - Zhang, Baoning (Chinese Journal of Cancer Research, 2013)
Objective: To evaluate the effect of operation timing during menstrual cycle on the prognosis of patients with breast cancer. Methods: 218 operated premenopausal patients with breast cancer had been followed-up for more than 10 years. Prognostic factors related to these patients had been selected to be underwent univariate analysis and multivariate analysis by Cox regression model. Results: Univariage analysis showed that the menstrual timing of operation, as other Known prognostic factors (tumor size, node status, histological grade, TNM classification, adjuvent systemic therapy, etc), had an influence on the patients' outcome. Multivariate analysis by Cox regression model indicated that disease-free rate and overall survival rate of patients operated during the periovulatory phase (123 cases) were significantly superior to those operated during the premenstrual phase (95 cases) (P0.01). Conclusion: Probably there is an optimal timing of operation for premenopausal breast cancer patients. Any prospective, randomized clinical study should be carried out to make this problem clear.